EMDR Therapy Modulates the Default Mode Network in a Subsyndromal, Traumatized Bipolar Patient - Landin-Romero, Ramon; Novo, Patricia; Vicens, Victor; McKenna, Peter J.; Santed, Antonia; Pomarol-Clotet, Edith; Salgado-Pineda, Pilar; Shapiro, Francine; Amann, Benedikt L. (Neuropsychobiology, 2013)
Background: Some functional imaging abnormalities found in bipolar disorder are state related, whereas others persist into euthymia. It is uncertain to what extent these latter changes may reflect continuing subsyndromal affective fluctuations and whether those can be modulated by therapeutic interventions. Method: We report functional magnetic resonance imaging (fMRI) findings during performance of the n-back working memory task in a bipolar patient who showed a marked improvement in subsyndromal affective symptoms after receiving eye movement desensitization and reprocessing (EMDR) therapy in the context of a clinical trial. Results: The patient's clinical improvement was accompanied by marked changes in functional imaging, as compared to 30 healthy subjects. fMRI changes were noted particularly in deactivation, with failure of deactivation in the medial frontal cortex partially normalizing after treatment. Conclusions: This case supports the potential therapeutic overall benefit of EMDR in traumatized bipolar patients and suggests a possible neurobiological mechanism of action: normalization of default mode network dysfunction.